Towards a standardized diabetic prolonged wound healing model in hairless SKH1 mice - Koivunotko, Elle; Monola, Julia; Pridgeon, Chris S.; Linden, Jere; Harjumäki, Riina; Yatkin, Emrah; Madetoja, Mari; Yliperttula, Marjo (Frontiers Media SA, 2026)
Chronic wounds, particularly those associated with diabetes, pose a significant clinical challenge due to their impaired healing dynamics and lack of reliable and standardized preclinical models. This pilot study aimed to establish a diabetogenic, immunocompetent, hairless mouse model (SKH1 strain) to simulate prolonged wound healing. Diabetes was induced by streptozotocin administration, followed by the creation of full-thickness dorsal skin wounds. Wounds were treated with either saline or nanofibrillated cellulose hydrogel as a model treatment. Wound healing progression and blood glucose were monitored, and histopathological assessments were performed after a 14-day experiment. In addition, for the first time, the Thermidas thermal imaging system was used in an in vivo mouse model to evaluate skin temperature. Results demonstrated that diabetes induction successfully prolonged wound closure by 5 days compared with the previously described acute wound model in the same strain with the identical protocol without streptozotocin (STZ) induction. Histopathological analyses showed increased macrophage activity (16.2% vs. 2.2% in the treatment groups and 10.2% vs. 0.3% in the control groups) and decreased collagen deposition (12.2% vs. 43.2% in the treatment groups and 17.6% vs. 27.4% in the control groups), suggesting prolonged wound healing. These findings support the use of hairless SKH1 mice as a viable model for studying prolonged diabetic wound healing and evaluating future therapeutic candidates.